Code Adventure: An Educational Game for Learning JAVA Programming - Uiphanit, Thanakorn; Janpla , Satien; Chutosri , Thatsanan; Liangyoo , Pongpisid; Wattanaprapa , Natcha; Kingsuwankul , Pongsakorn; Bunchongkien , Wannarat; Chiewchan , Phachaya; Intarapoo , Aekkaphob; Nititerapad, Chunyarat (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The purpose of this project is to (1) develop an educational game for learning in a JAVA programming course for undergraduate students, (2) compare the learning achievements of educational games and lectures, and (3) assess learner game acceptance with learning through games. The sample used in this research were 50 first-year undergraduate students in the field of management information systems from the Department of Information Science, S University in Thailand. In game design and development, The researcher developed the game based on the concept of game flow elements, such as challenges, story, fun, beauty, and so on, in order to inspire learners to be engaged in learning through games. The tools used in the research were (1) educational game performance evaluation forms, (2) an educational game for learning JAVA programming concepts, (3) a learning achievement test, and (4) student satisfaction assessment forms. The research results showed that (1) the learning efficiency of the educational game was very good, (2) the academic achievement of learning by the educational game was higher than that of learning by lecture, and (3) the acceptance of learning with computer games by the students was excellent. Additionally, learning through games made it easier for students to absorb the subject and learn more effectively. It has been discovered that learning through games improves learning results for students.